Comparação entre o ultrassom transperineal e o ultrassom anorretal tridimensional dinâmico na avaliação de disfunções do assoalho pélvico - Karbage, Sara Arcanjo Lino (2020)
Pelvic floor dysfunction (PFD) is a common condition, which affects about one third of adult women, with symptoms of genito-urinary and intestinal tracts. Women with obstructed defecation symptoms usually need further evaluation with imaging tests. The aim of this study was to compare the findings of transperineal ultrasound (TPUS) and dynamic threedimensional anorectal ultrasound (ecodefecography) in the assessment of PFD. Forty-two women with obstructed defecation symptoms were included in this study, even after dietary changes. Each patient was assessed with ecodefecography (EDF) combined with endovaginal approach and TPUS by different examiners. The accuracy of TPUS was assessed by calculating the agreement index (kappa index), considering EDF results as the gold standard. The mean age of the patients was 56 years, and the majority (69%) had a history of vaginal delivery. EDF combined with transvaginal ultrasound was superior in identifying sphincter defects and injury to the pubovisceral muscle. There was substantial agreement regarding the diagnosis of anismus (k = 0.688), perfect agreement with the diagnosis of rectocele (k = 0.892), reasonable agreement with the diagnosis of intussusception (k = 0.203) and perfect agreement with the diagnosis of cystocele (k = 0.850) between the two exams. The rectocele measurements obtained by TPUS were compared with those of EDF, and a new classification of rectocele was proposed. There was no correlation between the displacement of the puborectal muscle at maximum straining on EDF with the displacement of the anorectal junction on TPUS to determine perineal descent. It was concluded that there was a good correlation between the two techniques, with satisfactory agreement between TPUS and EDF for the diagnosis of anismus, rectocele and cystocele. A new classification of rectocele assessed by TPUS has been established.